Strategic Decisions: Behavioral Differences Between CEOs and Others - Håkan J. Holm; Victor Nee; Sonja Opper (Lund University, School of Economics and Management, Department of Economics, 2016)
Differences in strategic decision making between CEOs and other people are interesting since CEOs make important economic decisions and impact values and norms in society. Our study combines a large stratified random sample of 199 CEOs of medium-size firms with a carefully selected control group of 200 comparable people. All subjects participated in three different incentivized strategic games — Prisoner's Dilemma, Chicken, Battle-of-the-Sexes. We report substantial and robust differences in both behavior and beliefs between the CEOs and the control group. The CEOs are closer to the socially optimal strategy profile in all games. Hence, as a group the CEOs out-competes the control-group members and thereby receives higher average earnings, but not by being smarter (in the narrow "rationalistic" sense) or more selfish, but by being more cooperative and less aggressive.
Keywords: C70; C93; D22; L26; 330; Strategies; Efficiency; Nash equilibrium; Incentivized behavior; CEOs